Prevalence of Insulin Resistance, Dyslipidemia and Metabolic Syndrome in Infertile Women with Polycystic Ovary Syndrome - Ishrat, Shakeela; Hussain, Marufa (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Introduction: Polycystic ovary syndrome (PCOS) affects 5-10% of reproductive age women and it is a common cause of infertility in young women. Most of the infertile women with PCOS are overweight or obese with related risks of insulin resistance, dyslipidemia and metabolic syndrome. There is ethnic variation in the prevalence of obesity and its related metabolic abnormalities in women with polycystic ovary syndrome. This study was designed to explore the prevalence of insulin resistance, dyslipidemia and metabolic syndrome in infertile women with polycystic ovary syndrome in Bangladesh. Methods: This was a cross sectional study of 126 infertile women with polycystic ovary syndrome attending the Infertility unit of the Department of Obstertrics and Gynaecology at Bangabandhu Sheikh Mujib Medical University from January 2017 to December 2017. Results: The mean BMI was 26.58±3.18 and mean waist circumference was 91.07±9.5 cm. Regarding the prevalence of obesity, 47.6% of the women were overweight (BMI 23 - 27.5 kg/m2), 39.7% was obese (BMI>27.5 kg/m2) and central obesity (waist circumference ≥80 cm) was in 80.2%. In infertile women of PCOS, the prevalence of insulin resistance was 27.8% , dyslipidemia 93.7% metabolic syndrome 42.9% .Median fasting insulin was higher than the cut off for insulin resistance specific for south Asian population. Insulin resistance measured by hyperinsulinemia was much more frequent (65.9%) than that measured by HOMA-IR (27.8%).The most common lipid abnormality was low HDL cholesterol (90.5%) followed by elevated LDL-cholesterol (79.4%). Low HDL cholesterol (90.5%) and abdominal or central obesity (80.2%) were the most common criteria of metabolic syndrome. There is increasing trend in metabolic syndrome with age. Conclusion: Screening the infertile women with polycystic ovary syndrome for insulin resistance, dyslipidemia and metabolic syndrome is important because it allows for additional counseling about long term health consequences and emphasis on weight management. J Bangladesh Coll Phys Surg 2021; 39: 225-232